Case Report: A case of unexplained retinoschisis - Wang, Nan; Zhang, Yu; Yuan, Fuxiang; Zhao, Chunning; Zhou, Zhanyu (Frontiers in Medicine, 2025)
BackgroundRetinoschisis is characterized by separation of the neurosensory retina into two layers. The traditional pars plana vitrectomy with internal limiting membrane peeling and macular buckling has been shown to resolve retinoschisis. We report a case of unknown cause of retinoschisis in a young adult.Case presentationA 24-year-old man presented with an 18-day history of metamorphopsia and blurred vision in his left eye. Optical coherence tomography revealed retinoschisis in the macula, the temporal side of the macula, and near the superior and inferior vascular arches. The patient was treated with oral corticosteroids. His clinical characteristics and status of retinoschisis were monitored at each visit. The retinoschisis initially became aggravated; however, it had completely resolved by the 40-day follow-up visit.ConclusionClinicians should be aware that, for patients with clinically identified posterior vitreous detachment (PVD) without vitreomacular traction (VMT), follow-up observation or empirical treatment with glucocorticoids can be considered to observe the disease outcome.